Uporaba metode električne upornosti tal na primeru Divaške jame - Mihevc, Andrej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2011)
Electrical resistivity imaging (ERI) is a widely used tool in geophysical survey of various subsurface structures. To establish its applicability for karst subsurface, ERI was conducted in Divača karst above caves of Trhlovca and Divaška jama and in its continuation as denuded cave on slopes of Radvanj collapse doline. Empty cave passages were not detected with ERI as electrical resistivity difference between voids and highly resistive carbonate bedrock is too small. On the other hand, denuded caves and cave sections, filled with loamy material, can be clearly distinguished.
Keywords: Divaška jama; electrical resistivity imaging; električna upornost; geomorfologija; geomorphology; karst caves; karstology; krasoslovje; kraške jame; List of caves in Slovenia; metode; Slovenia; Slovenija; tla